Why did Ukraine become a Key Player on the World Agri-Food Markets? An Enterprise-Level Perspective - Taras Gagalyuk; Igor Ostapchuk; Volodymyr Lapa; Alfons Balmann (German Journal of Agricultural Economics (GJAE), 2022)
Over the past decades, Ukraine has built an increasingly dynamic agricultural sector, characterized by growing export engagement in various commodities. Whether the country can quickly regain its status of a key player on the world agri-food markets amid and after Russian invasion is extremely important for international food security. However, the to-date understanding of the recovery potential remains elusive due to the lack of systematic and objective insights into the major drivers of recent growth. Scarce evidence suggests that Ukraine's agriculture has been successfully modernized mainly due to the efforts of private sector actors operating in the context of generally inconsequent policies typical of a transition country. The following factors have been reported to contribute to recent modernization and development of the sector: a) improvement of efficiency and productivity, especially in crop production; b) structural change involving a rapid development of large-scale agroholdings; and c) relatively positive public acceptance of modern technologies and organizational forms of agricultural production. The present paper reviews these trends in greater detail by addressing the role of professional farm management, digital technologies, ongoing optimization of the size of production operations (including horizontal and vertical integration through merger and acquisitions) as well as farm engagement in sustainability and legitimation activities as the main enterprise-level drivers of growth and resilience in Ukrainian agriculture.
Keywords: 330; agricultural enterprises; financial strength; digitaliza-tion; resilience; structural change; Ukraine